ADSORPSI ION KALSIUM MENGGUNAKAN BIOMASSA ECENG GONDOK (Eichhornia crassipes) DIREGENERASI HCL - Rakhmania, Citra Dewi; Khaeronnisa, Indah; Ismuyanto, Bambang; Nanda, Julia; Himma, Nurul Faiqotul (Fakultas Teknik, Universitas Brawijaya, 2017)
Water hyacinth (Eichhornia crassipes) is known as an aquatic weed that has rapid growth. However, the water hyacinth has the ability to remove metals from water as it acts as a natural adsorbent. Calcium ion is one of the metallic ions which can cause hardness and scaling in high temperature, resulting in a decrease of the efficiency of industrial equipment. In this research, the water hyacinth was regenerated with HCl and used as an adsorbent to adsorb calcium ion. The effect of HCl concentration and calcium ion concentration on the adsorption capacity of calcium ion was investigated. The results show that adsorption capacity of calcium ion increased as the concentration of HCl increased up to 3 M. At higher concentration of HCl, 4 M and 5 M, the adsorption capacity decreased because some functional groups of hydroxyl and carboxyl which play an important role in adsorption process are cleavage. Maximum adsorption capacity was achieved at 38,733 mg Ca/gr adsorbent with regeneration of adsorbent at HCl 3M and 500 ppm of calcium ion